Extracellular vesicle integrins act as a nexus for platelet adhesion in cerebral microvessels - Bagi, Z; Couch, Y; Broskova, Z; Perez-Balderas, F; Yeo, T; Davis, S; Fischer, R; Sibson, N; Davis, B; Anthony, D (Nature Research, 2019)
Circulating extracellular vesicles (EVs) regulate signaling pathways via receptor-ligand interactions and content delivery, after attachment or internalization by endothelial cells. However, they originate from diverse cell populations and are heterogeneous in composition. To determine the effects of specific surface molecules, the use of synthetic EV mimetics permits the study of specific EV receptor-ligand interactions. Here, we used endogenous EVs derived from the circulation of rats, as well as ligand-decorated synthetic microparticles (MPs) to examine the role of integrin αvβ3 in platelet adhesion under flow in structurally intact cerebral arteries. At an intraluminal pressure of 50 mmHg and flow rate of 10 µl/min, platelets were delivered to the artery lumen and imaged with whole-field fluorescent microscopy. Under basal conditions very few platelets bound to the endothelium. However, adhesion events were markedly increased following the introduction of arginine-glycine-aspartate (RGD)-labelled synthetic MPs or endogenously-derived EVs from experimental stroke animals carrying excess RGD proteins, including vitronectin, CD40-ligand and thrombospondin-1. These data, which were generated in a dynamic and physiologically relevant system, demonstrate the importance of vesicle-carried RGD ligands in platelet adherence to the cerebrovascular endothelium and highlight the ability of synthetic EVs to isolate and identify key components of the molecular handshake between EVs and their targets.